2018
DOI: 10.4028/www.scientific.net/msf.928.123
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Rare-Earth Photoanode Doping on Dye-Sensitised Solar Cell Electrical Performance

Abstract: Renewable energy sources, such as solar energy, could potentially provide an affordable alternative to conventionally generated electricity, especially in locations like the Caribbean which tend to have an abundant solar resource, but also high cost for electricity. Thin film and hybrid solar devices, including Dye-Sensitized Solar Cells (DSSCs), are especially promising energy solutions, due to the low cost of materials and equipment required for their fabrication. In this paper, we investigate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In 2018, Henderson et al investigated the effect of RE lanthanum, cerium, and praseodymium‐doped TiO 2 ‐based DSSC photoanodes on the overall performance of the cell. Their experimental study revealed that TiO 2 doped with 2% concentration of lanthanum and sintered at 400 °C for 30 min exhibit the maximum efficiency (increased by 39%) of DSSCs as compared to undoped photoanodes in DSSCs According to another recent report, Xing et al observed that 0.050 g‐Ce/TiO 2 as photoanode material shows maximum energy conversion efficiency in DSSCs, in comparison to pristine TiO 2 and TiO 2 samples with different Ce%.…”
Section: Re‐doped Tio2 For Spectral Conversionmentioning
confidence: 98%
“…In 2018, Henderson et al investigated the effect of RE lanthanum, cerium, and praseodymium‐doped TiO 2 ‐based DSSC photoanodes on the overall performance of the cell. Their experimental study revealed that TiO 2 doped with 2% concentration of lanthanum and sintered at 400 °C for 30 min exhibit the maximum efficiency (increased by 39%) of DSSCs as compared to undoped photoanodes in DSSCs According to another recent report, Xing et al observed that 0.050 g‐Ce/TiO 2 as photoanode material shows maximum energy conversion efficiency in DSSCs, in comparison to pristine TiO 2 and TiO 2 samples with different Ce%.…”
Section: Re‐doped Tio2 For Spectral Conversionmentioning
confidence: 98%